PENGARUH PROGRAM COACHING, MENTORING, DAN COUNSELING TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) UP3 PEKALONGAN : Penelitian - Riyanti; Arif Budiharjo; Latief Z. Nur (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
PT. PLN (Persero) UP3 Pekalongan optimizes the performance of its employees by implementing the CMC (Coaching, Mentoring, Counseling) leadership program, where a leader helps employees motivate, pays attention to employees at work, and becomes a role model for employees. And this CMC Program is expected to improve the Performance of PT Management Employees. PLN (Persero) UP3 Pekalongan, developed this CMC strategy or program to support skills development and increase employee performance. This research aims to determine the influence of the superior CMC (Coaching, Mentoring, Counseling) program in supporting employee performance at PT PLN (Persero) UP3 Pekalongan. This research is quantitative research, and is causal in nature. There were 40 respondents in the population, namely a number of employees at PT PLN UP3, and all of them were used as samples, or in other words the sample used was a saturated sample. Data collection was carried out using a questionnaire. This research uses multiple regression analysis tools. The results of this research are: Coaching and Mentoring have a positive and insignificant effect on the performance of PT PLN (Persero) UP3 Pekalongan employees and Counseling has a significant positive effect on the performance of PT PLN (Persero) UP3 Pekalongan employees.